(untitled) (Journal of Governance and Development (JGD), 2025)
Many Nigerian women are deeply concerned about the low level of women’s political mobilization in Nigeria over the decades. To address this issue, this study investigates the causes of the low level of women’s political participation in Nigerian politics. This paper employed a case study design, focusing on historical antecedents and a time frame from 1999 to the present. As a form of methodology, the research uses secondary sources from the internet, government publications, newspapers, journals, and pertinent textbooks. The findings of this study are that socioeconomic variables cause low levels of women’s mobilization in political activities in Nigeria, the nation’s cultural heritage, historical legacies, and instructional design considerations. The study highlights how important it is to deal with the issues that support women’s subordination in Nigeria’s political structure. As a result, the study concludes that all religious statutes, customs, and ordinances that hinder women’s political mobilization must be changed, and that explicit implementation guidance must be provided. The need to foster greater mobilization efforts and empowerment motivated the whole essential of women’s political mobilization in Nigeria due to long years of neglect.